Petrographic and geochemical evidence for multiphase formation of carbonates in the Martian orthopyroxenite Allan Hills 84001. (10th March 2017) - Moyano‐Cambero, Carles E.; Trigo‐Rodríguez, Josep M.; Benito, M. Isabel; Alonso‐Azcárate, Jacinto; Lee, Martin R.; Mestres, Narcís; Martínez‐Jiménez, Marina; Martín‐Torres, Francisco J.; Fraxedas, Jordi
Abstract: Martian meteorites can provide valuable information about past environmental conditions on Mars. Allan Hills 84001 formed more than 4 Gyr ago, and owing to its age and long exposure to the Martian environment, and this meteorite has features that may record early processes. These features include a highly fractured texture, gases trapped during one or more impact events or during formation of the rock, and spherical Fe‐Mg‐Ca carbonates. In this study, we have concentrated on providing new insights into the context of these carbonates using a range of techniques to explore whether they record multiple precipitation and shock events. The petrographic features and compositional properties of these carbonates indicate that at least two pulses of Mg‐ and Fe‐rich solutions saturated the rock. Those two generations of carbonates can be distinguished by a very sharp change in compositions, from being rich in Mg and poor in Fe and Mn, to being poor in Mg and rich in Fe and Mn. Between these two generations of carbonate is evidence for fracturing and local corrosion.